Pengaruh Perencanaan Manajemen Sumber Daya Manusia Terhadap Kinerja Organisasi - Hartono, Ardhit Wiro; Putra, Viko Rachmatullah (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2025)
This study aims to analyze the impact of..human resource planning on organizational performance. HR planning is the key element in workforce management to ensure organizational effectiveness and efficiency. Method of this research used literature review referring to various previous studies. The results show that effective HR planning can increase productivity, reduce employee turnover, and enhance job satisfaction. These findings indicate that companies need to adopt adaptive HR planning strategies to address globalization challenges and technological advancements.